PENGARUH KOMITMEN PROFESIONAL AUDITOR TERHADAP INTENSI MELAKUKAN WHISTLEBLOWING: LOCUS OF CONTROL SEBAGAI VARIABEL PEMODERASI (STUDI EMPIRIS PADA KANTOR AKUNTAN PUBLIK DI JAKARTA) - , Fitri Yani Jalil; , Dr. Mahfud Sholihin, M.Acc., ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study examines the impact of auditorâs profesional commitment to the whistleblowing intention. This study also submits the locus of control as mederating effect in the relationship. This study modified by using sample of real auditor where former research uses auditing student. The used data is 105 of junior and senior external auditors from public accounting firm in Jakarta. The result indicates that there is no significance impact neither from professional commitment nor the mederating effect of locus of control to the whistleblowing intention. It means that professional commitment and locus of control canât raise the whistleblowing intention of real auditor and suppose other factors become a barrier to whistleblow.